PRAGMATIC FAILURE DALAM PENERJEMAHAN KOMIK TINTIN â€“ FLIGHT 714 - Azshary Sidiq; Diba Artsiyanti E P (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This study focuses on the analysis of pragmatic failure in HÃ©rge's comic The Adventure of Tintin and its translation the analysis involves the discussion of pragmatic failure, pragmatics in context, as well as the translation process of SL (source language) to TL (target language). The method used in this study is qualitative comparative The Data was collected from one of The Adventure of Tintin Comics series; Flight 714. The results indicated that there were two pragmatic failure, pragmalinguistic and sociopragmalinguistic in the translation of the comics. In addition, in the translation of comics found pragmatic failure in the translation process in the process of analysis, transfer and restructuring. In addition, research results also show that pragmatic failure occurs including pragmatics; speech situations, speaker and hearer, speech context, goals of speech, implicature and deixis. In addition, translations related to pragmalinguistic, sociopragmatic, and psycholinguistic because to translate English into Indonesia cannot separated it all. In order to produce a good translation by understanding the context when translating.